Perancangan Penyusunan Laporan Keuangan Konsolidasi - Tri Irawati, Sri Harjanto (Jurnal Ilmiah SINUS, 2014)
The importance of financial statements prepared by all levels of the organization do not miss all the UMKM that have multi-run business. Technological developments provide various means preparation of financial statements in the method. Facilitate the development of this technology UMKM need to understand the design and design in the preparation of financial statements that will be used. The design of UMKM is expected to develop in the creation of applications that will be developed in accordance with the capabilities of the UMKM. Simulation of the settlement accounting to the preparation of financial statements reference manual that can be used in the preparation design and design required. The design consists of a suggested flowchart document, context diagrams, HIPO, data flow diagrams, database design, input and output design.